REASONS FOR PLACING A STENT IN THE HEART (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Medicine has been going through a period of positive change since the last century. A stent is a small metal mesh tube that keeps your artery open to improve blood flow. Stents often help people with blocked coronary (heart) arteries. Metal and fabric stent grafts treat aortic aneurysms. Most stents are permanent. You may need to take medication to reduce the risk of blood clots after a stent is placed. This article provides information about the types of stents, the heart benefits, and skills and knowledge for patients who use stents.